Effect of Application of Guava Leaf Extract (Psidium guajava L.) on Tobacco Mosaic Virus (TMV) Attack on Red Chili (Capsici annum L.) - Yugista, Serdinia; Martosudiro, Mintarto; Choliq, Fery Abdul (University of Brawijaya, 2023)
Red chili (Capsici annum L.) is a significant horticultural commodity widely consumed in Indonesia. From 2016 to 2020, red chili production consistently increased, reaching 1,264,190 tons in 2020. Despite this growth, certain regions still face production shortfalls relative to consumption needs. A major challenge in red chili cultivation is the Tobacco Mosaic Virus (TMV), which remains difficult to control as no pesticides currently target plant viruses directly. This study investigated the impact of guava leaf extract (Psidium guajava L.) on the incubation period, severity of TMV infection, and growth parameters in red chili plants. The experiment utilized a complete randomized design comprising six treatments with four replications, each involving two plants. The results indicate that four applications of guava leaf extract extended the TMV incubation period to 19.25 days post-inoculation and reduced attack intensity by 4.93%. Additionally, this treatment enhanced plant growth, evidenced by increased plant height and leaf number, and was the only treatment classified as resistant compared to other tested methods.